2022
DOI: 10.3847/1538-4357/aca09d
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Initial–Final Mass Relations on Black Hole Microlensing

Abstract: Uncertainty in the initial–final mass relation (IFMR) has long been a problem in understanding the final stages of massive star evolution. One of the major challenges of constraining the IFMR is the difficulty of measuring the mass of nonluminous remnant objects (i.e., neutron stars and black holes). Gravitational-wave detectors have opened the possibility of finding large numbers of compact objects in other galaxies, but all in merging binary systems. Gravitational lensing experiments using astrometry and pho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 75 publications
2
4
0
Order By: Relevance
“…Note that our results use a higher cadence than the Lam et al (2020) "v3" results, catching more events with long duration. However, when running our simulations without PBHs using the exact same simulation parameters as Lam et al (2020), we find identical results to those reported in Lam et al (2020, Appendix A.1) and by Rose et al (2022).…”
Section: Mock Ogle-ivsupporting
confidence: 87%
See 1 more Smart Citation
“…Note that our results use a higher cadence than the Lam et al (2020) "v3" results, catching more events with long duration. However, when running our simulations without PBHs using the exact same simulation parameters as Lam et al (2020), we find identical results to those reported in Lam et al (2020, Appendix A.1) and by Rose et al (2022).…”
Section: Mock Ogle-ivsupporting
confidence: 87%
“…The Stellar Population Interface for Stellar Evolution and Atmospheres, or SPISEA, is a Python package used to generate star clusters (single-age and single-metallicity populations) using various input parameters, including age, mass, metallicity, extinction, atmospheric models, and initial mass functions (Hosek et al 2020). SPISEA allows for compact object generation by supporting user control of the initial-final mass relation (IFMR; Rose et al 2022). We follow the SPISEA modifications outlined in Lam et al (2020) Section 2.2, which uses the Raithel18 (Raithel et al 2018) IFMR from recent simulations, along with the zero-age mainsequence (ZAMS) mass of each star, in order to build a population of stellar evolved BHs, neutron stars (NSs), and white dwarfs (WDs).…”
Section: Spiseamentioning
confidence: 99%
“…One important outcome of the star formation history of the NSC is that it allows us to predict the type and number of compact objects including SBHs, NSs, and WDs. We calculate the predicted number of compact objects via SPISEA with our derived star formation history, the first metallicity constraints on the NSC, realistic multiplicity properties (Lu et al 2013), and the metallicity-dependent initial-final mass relation (IFMR) implemented by Rose et al (2022; the Spera15 IFMR object within SPISEA).…”
Section: Mass Comparison With Dynamical Constraintsmentioning
confidence: 99%
“…SPISEA generates SOBHs, NSs, and WDs by evolving clusters matching each subpopulation of stars generated by Galaxia (thin and thick disk, bulge, stellar halo), assuming they are single-age, and single-metallicity populations and then injects the resulting compact objects into the simulation. SPISEA uses an initial mass function, stellar multiplicity, extinction law, metallicity-dependent stellar evolution, and an initial final mass relation (IFMR; see, e.g., Rose et al 2022). Separate IMFRs are used for NSs and SOBHs (see Appendix C of Lam et al 2020) and WDs (Kalirai et al 2008).…”
Section: Galactic Model and Stellar Evolutionmentioning
confidence: 99%